Why do Passengers Continue to use the Trans Jatim Bus? The Mediating Role of User Satisfaction in the Effects of Service Quality and Customer Experience in Lamongan Regency - Evi Yulia; Muhamad Imam Syairozi (Sean Institute, 2026)
This study aims to analyze the effects of service quality and customer experience on the intention to reuse the Trans Jatim Bus, with user satisfaction as a mediating variable. A quantitative approach was employed using a survey of 170 users of Trans Jatim Bus Corridor VII in Lamongan Regency, selected through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that service quality has a positive effect on user satisfaction but has no direct effect on reuse intention. In contrast, customer experience has a positive and significant effect on both user satisfaction and reuse intention. User satisfaction also has a positive effect on reuse intention, fully mediates the relationship between service quality and reuse intention, and partially mediates the relationship between customer experience and reuse intention. These findings indicate that improvements in service quality need to be accompanied by the creation of positive user experiences to increase satisfaction and encourage continued use of the Trans Jatim Bus service. This study contributes to the development of Expectation Confirmation Theory in the context of public transportation and provides practical input for Trans Jatim Bus operators seeking to strengthen user loyalty.